Forgiveness and its reason - Jesson, S.N. (2011)
Forgiveness might be said to involve a certain kind of intellectual suffering: we forgive, and are forgiven, whilst a great many questions remain undecided, and while it is far from obvious that they are unimportant. This thesis explores the way in which the difficulties in submitting forgiveness to thought may be significant. Contemporary accounts of forgiveness are put into creative dialogue with the work of Simone Weil, Rene Girard and Jacques Derrida in an attempt to assess different forms of approach to the resistance forgiveness offers to thought. Utilising the work of Simone Weil in particular, and through a creative interpretation of some of the gospel sayings from which the modern notion of forgiveness originates, the argument is made that forgiveness can be seen to involve a process of transformation of understanding that is akin to spirituality of death and resurrection. On this account, forgiveness is paradoxical and resistant to thought not because it involves a simple suspension of, or opposition to reasoned forms of judgment, but because it involves a way of holding together attitudes, concerns and insights that do not easily cohere. As such it calls for a ‘posture’ that cultivates and waits with this tension, rather than a theory that allows the meaning and goodness of forgiveness to appear unambiguously. In this sense forgiveness is an expression of a love that both hopes all things and bears all things; a way of accepting the worst whilst desiring the best.